(untitled) (Journal of Material Science and Technology Research, 2023)
Abstract: Bismuth sodium titanate, denoted as Bi0.5Na0.5TiO3-BaTiO3 (BNT-BT), possessing a perovskite-like structure, has emerged as a highly prospective material in recent years. It is considered a prime contender for replacing PZT-based compounds due to its exceptional piezoelectric and ferroelectric properties, coupled with the presence of loosely bound pairs of chemically active electrons. This study delves into the micromorphological properties of BNT-BT thin film electrodes, fabricated using sol-gel spin-coating and subsequent annealing processes. Employing Atomic Force Microscopy (AFM), comprehensive 2D and 3D topographical maps were acquired, enabling the extraction of pivotal parameters crucial for surface characterization. Notably, the investigation encompasses Minkowski Functionals, which encompass normalized Minkowski volume, boundary, and connectivity analyses. In conjunction, various roughness parameters, encompassing arithmetic mean height, maximum peak height, maximum valley depth, arithmetic mean depth, and the ten-point height parameter, were quantified across these analyses to facilitate a comprehensive comparison of surface morphologies among distinct samples. The morphological analysis outcome underscores the potential for elucidating material performance through microstructural shape and quantitative roughness evaluation of respective surfaces. This holds significant promise for applications such as predictive assessment of functional behavior, including industrial quality control during sample manufacturing processes.